Strategic Steps To Make Effective National Energy Conservation Movement - Myson Myson (Information Technology and Science (ITScience), 2024)
The aim of this research is energy conservation as a pillar of national energy management which has not received adequate attention in Indonesia. The method used in this writing is qualitative descriptive. This method is used to describe the facts in the field. The results achieved in this research are the increasingly popular idea of ??using energy economically as a